2001
DOI: 10.1161/hy1001.092615
|View full text |Cite
|
Sign up to set email alerts
|

Lipids Stimulate the Production of 6-keto-prostaglandin F in Human Dorsal Hand Veins

Abstract: Abstract-Obese hypertensives have increased nonesterified fatty acids (NEFAs) and ␣-adrenergic vascular reactivity.Raising NEFAs locally with intralipid and heparin augments dorsal hand venoconstrictor responses to phenylephrine, an ␣ 1 -adrenoceptor agonist. The enhanced venoconstrictor responses were reversed by indomethacin. The findings suggest that raising NEFAs leads to the generation of cyclooxygenase (COX) product(s) that enhance vascular reactivity. To test this notion, 6-keto-PGF 1␣ and TxB 2 , the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…In previous studies in dorsal hand veins of healthy normotensive subjects, we observed a lipid-associated enhancement in a 1 vasoreactivity [9] and endothelium-dependent venodilation abolished by indomethacin [10]. Subsequent studies revealed the local generation of the stable prostacyclin derivative, 6-keto-PGF 1a induced by lipids [25]. Complementary invitro studies showed that 2 cis-unsaturated fatty acids, oleic and linoleic acid enhanced in 6-keto-PGF 1a corresponding with increased calcium influx into cultured vascular smooth muscle cells, which presumably activated phopholipase A2 with the release of arachidonic acid and the generation of eicosanoid products.…”
Section: Discussionmentioning
confidence: 65%
“…In previous studies in dorsal hand veins of healthy normotensive subjects, we observed a lipid-associated enhancement in a 1 vasoreactivity [9] and endothelium-dependent venodilation abolished by indomethacin [10]. Subsequent studies revealed the local generation of the stable prostacyclin derivative, 6-keto-PGF 1a induced by lipids [25]. Complementary invitro studies showed that 2 cis-unsaturated fatty acids, oleic and linoleic acid enhanced in 6-keto-PGF 1a corresponding with increased calcium influx into cultured vascular smooth muscle cells, which presumably activated phopholipase A2 with the release of arachidonic acid and the generation of eicosanoid products.…”
Section: Discussionmentioning
confidence: 65%
“…Therefore, the level of 6-keto-PGF1α, a stable metabolite produced by PGI 2 , can not only refl ect the condition of platelet aggregation inhibition, but also reflect the injury degree of vascular VECs. (28,29) The present research shows that VECs secretion function and fibrinolysis function were regulated in the daiclzein group and Danhong Injection group as compared with hypoxia group.…”
Section: Discussionmentioning
confidence: 55%
“…Our results showed that the dose of phenylephrine needed to reach ED 70% was higher after the OLO, characterizing an α 1 -adrenergic response alteration, which is demonstrated for the first time in healthy adults. Studies of venous endothelial function in response to the infusion of free fatty acids showed increased α 1 -adrenergic reactivity [32] together with an increased pressoric response, probably due to increased intracellular Ca 2+ activated by phospholipase A 2 [33]. In these studies, increased α 1 -adrenergic reactivity was characterized by the lower dose of phenylephrine needed to achieve the vasoconstrictor and pressoric response.…”
Section: Discussionmentioning
confidence: 75%